Demotivating Factors in Learning English: Students’ Perceptions - Lutfiyan Khusyabaroh; Utami Widiati; Mirjam Anugerahwati (Jurnal Pendidikan Humaniora, 2018)
Abstract: Students’ demotivation is an area which is not widely reached from studies. It is essential to revover the students’ demotivation factors in learning English. 240 ninth grade of junior high schools students were taken part. There were four factors of demotivation, they were seen from teacher, classmates, text books and activities, and students’ characteristics aspects.Key Words: students’ demotivation, learning English, perceptionsAbstrak: Demotivasi siswa merupakan topik yang belum begitu tersentuh oleh penelitian. Oleh karena itu, penting untuk menguak penyebab demotivasi siswa dalam belajar bahasa Inggris. Ada 240 siswa yang bersedia menjadi sampel penelitian ini. Hasil penelitian menemukan empat faktor demotivasi siswa, yaitu aspek giri, teman sekelas, buku pelajaran dan kegiatan, dan karakteristik siswa.Kata kunci: demotivasi siswa, belajar bahasa Inggris, persepsi